Selective Spin Dewetting for Perovskite Solar Modules Fabricated on Engineered Au/ITO Substrates - Son Singh; Rahim Abdur; Md. Abdul Kuddus Sheikh; Bhabani Sankar Swain; Jindong Song; Jae-Hun Kim; Ho-Seok Nam; Sung-Hyon Kim; Hyunseung Lee; Jaegab Lee (Nanomaterials, 2024)
We introduce a novel method for fabricating perovskite solar modules using selective spin-coating on various Au/ITO patterned substrates. These patterns were engineered for two purposes: (1) to enhance selectivity of monolayers primarily self-assembling on the Au electrode, and (2) to enable seamless interconnection between cells through direct contact of the top electrode and the hydrophobic Au connection electrode. Utilizing SAMs-treated Au/ITO, we achieved sequential selective deposition of the electron transport layer (ETL) and the perovskite layer on the hydrophilic amino-terminated ITO, while the hole transport layer (HTL) was deposited on the hydrophobic CH3-terminated Au connection electrodes. Importantly, our approach had a negligible impact on the series resistance of the solar cells, as evidenced by the measured specific contact resistivity of the multilayers. A significant outcome was the production of a six-cell series-connected solar module with a notable average PCE of 8.32%, providing a viable alternative to the conventional laser scribing technique.